Preventing anastomotic leakage after laparoscopic intersphincteric resection without a diverting stoma: "pull‐through/reborn". Issue 2 (13th July 2020) - Hamamoto, Hiroki; Okuda, Junji; Yamamoto, Masashi; Masubuchi, Shinsuke; Ishii, Masatsugu; Osumi, Wataru; Tanaka, Keitaro; Uchiyama, Kazuhisa
Abstract: Introduction: Patients with very low rectal cancer who undergo intersphincteric resection (ISR) often experience anastomotic leakage (AL), even with a diverting stoma. The aim of this study was to introduce a technique for anastomosis after laparoscopic ISR to avoid AL. Materials and Surgical Technique: In the first ISR procedure, the rectum was mobilized, the mesorectum was excised, and total, subtotal, or partial internal sphincter incision was performed transanally. In the second surgery, the adhesions between the prolapsed colon and the anal canal were bluntly dissected only as needed for suturing. After sufficient blood flow was confirmed using indocyanine green fluorescence imaging, coloanal transanal anastomosis was performed without a diverting stoma. We call this method "pull‐through/reborn". Discussion: "Pull‐through/reborn" method can prevent AL after laparoscopic ISR. However, more cases and more experience are necessary to analyze anal functions after this method is applied.